2011
DOI: 10.1111/j.1538-7836.2011.04207.x
|View full text |Cite
|
Sign up to set email alerts
|

Osteoprotegerin, a new actor in vasculogenesis, stimulates endothelial colony‐forming cells properties

Abstract: Summary. Background: Osteoprotegerin (OPG), a soluble receptor of the tumour necrosis factor family, and its ligand, the receptor activator of nuclear factor-jB ligand (RANKL), are emerging as important regulators of vascular pathophysiology. Objectives: We evaluated their effects on vasculogenesis induced by endothelial colony-forming cells (ECFC) and on neovessel formation in vivo. Methods: Effects of OPG and RANKL on in vitro angiogenesis were evaluated after ECFC incubation with OPG or RANKL (0-50 ng mL). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 48 publications
3
48
0
Order By: Relevance
“…Although the potential impact of the OPG-RANKL-TRAIL axis on risk of cancer and cancerrelated mortality has been comprehensively studied in experimental models (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), few data are available from observational and interventional studies in humans. Previously, we observed an association between serum OPG and mortality from non-vascular causes in the general population (HR 1.31, 95% CI 1.22-1.41) (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the potential impact of the OPG-RANKL-TRAIL axis on risk of cancer and cancerrelated mortality has been comprehensively studied in experimental models (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), few data are available from observational and interventional studies in humans. Previously, we observed an association between serum OPG and mortality from non-vascular causes in the general population (HR 1.31, 95% CI 1.22-1.41) (16).…”
Section: Discussionmentioning
confidence: 99%
“…OPG synthesized by monocytes within tumors may promote survival of several tumor cell types (5-7), and in vitro studies indicate that OPG may act as a survival factor for tumor cells in both solid tumors (5,8) and hematological malignancies (7), and induce angiogenesis (9,10). TRAIL induces apoptosis in a variety of cells, and tumor cells are more sensitive than non-malignant cells (9,11,12), whereas RANKL is involved in development and metastasis of breast cancer (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed the inhibitory effect of OPG on vascular calcification in animal models could be passive or cellular. As mentioned above, OPG exerts an antiapoptotic effect towards TRAIL and decreases in consequence the number of apoptotic bodies that may serve as nucleation sites for passive mineralization (Fleishman et al 1990;Benslimane-Ahmim et al 2011). Several studies have shown also that recombinant OPG can promote the survival/proliferation of mature vascular endothelial cells (Malyankar et al 2000;Pritzker et al 2004;Cross et al 2006;Kobayashi-Sakamoto et al 2006;McGonigle et al 2009).…”
Section: Rankl and Trail: Ligands From The Tnf Familymentioning
confidence: 99%
“…Moreover, if these results are in agreement with previous data describing VEGF as a target gene for ERRa in breast cancer (42), we show for the first time a positive association between high levels of ERRa and VEGF in breast tumors from patients (P ¼ 0.002; Table 1). Interestingly, OPG expression that can be stimulated by VEGF in endothelial cells, is also known to be a positive regulator of microvessel formation in vivo (43) and therefore can participate to the neovascularization observed in WT-1 tumors. We also observed that ERRa promoted BO2 breast cancer cell invasion in vitro ( Supplementary Fig.…”
Section: Erra Stimulates Tumor Growth and Angiogenesis In Vivomentioning
confidence: 99%